2010
DOI: 10.1002/anie.201000901
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Reactivity of a Stabilized Phosphiranylium Salt

Abstract: Charged! Combining MeBABAR‐Phos and methyl triflate affords an amino‐stabilized phosphiranylium ion (see picture; C gray, N blue, P orange), which undergoes various nucleophilic addition reactions to give P‐substituted phosphiranes and an N‐heterocyclic carbene stabilized phosphiranylium cation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…This bonding formulation has previously been proposed for relatedp hosphorus-containing compounds. [32][33][34] It is interesting to note that while 1a reacts with HOTf to afford ap hosphorus(III) compound with ap rotonated ligand backbone( 6a), the analogous reaction with an acidt hat has am ore nucleophilic counter-anion, such as HCl, affords the phosphorus(V) species HPCl(ONO) (8a). This differencei nr eactivity suggests that mechanistically,asufficientlys trongn ucleophile is required to afford the formal phosphorus(V) oxidative addition product.…”
Section: Reactivity Of 1a and 1b Towardselectrophilesmentioning
confidence: 99%
“…This bonding formulation has previously been proposed for relatedp hosphorus-containing compounds. [32][33][34] It is interesting to note that while 1a reacts with HOTf to afford ap hosphorus(III) compound with ap rotonated ligand backbone( 6a), the analogous reaction with an acidt hat has am ore nucleophilic counter-anion, such as HCl, affords the phosphorus(V) species HPCl(ONO) (8a). This differencei nr eactivity suggests that mechanistically,asufficientlys trongn ucleophile is required to afford the formal phosphorus(V) oxidative addition product.…”
Section: Reactivity Of 1a and 1b Towardselectrophilesmentioning
confidence: 99%
“…It was obtained by displacement of the intramolecular tertiary amine ligand of the phosphiranylium complex 9 by the independently generated NHC, acting as a stronger donor than the amine (Scheme 5). 29 It is noteworthy that both 9 and 10 can also be described by their amoniophosphine and carbeniophosphine Lewis structures, respectively. DFT studies of 10 confirmed the strong s-donation of the NHC lone pair to the empty p orbital of the phosphenium center, but revealed a small p-back-donation of the phosphenium lone pair competing with the nitrogen lone pairs in their interaction with the empty p z * orbital of the sp 2carbon atom.…”
Section: Imidazoliophosphine Systemsmentioning
confidence: 99%
“…The Grützmacher group reported the synthesis, structures, and reactivities of very stabilized phosphiranes, and phosphiranium and phosphiranylium salts via an approach of incorporating the PC2 cycle within a polycyclic framework (Figure 28). [199][200][201][202] 5-Dibenzosuberenone (1) was used as a platform for the synthesis of the highly strained dibenzophosphasemibullvalene 356, 199 very robust phosphaazabarbaralanes (BABAR-Phos) as 357, which was named in a manner analogous to the hydrocarbon 360 (barbaralane), 200 the phosphiranium ion 358, 201,202 and phosphiranylium salt 359. 202 The straightforward synthesis of BABAR-Phos 357 is shown in Scheme 59.…”
Section: Scheme 58 Reactions Of Tris(trimethylsilyl)silyllithium Withmentioning
confidence: 99%
“…201 Treatment of the corresponding N-methyl-BABAR-Phos resembling 357 with methyl triflate as a strongly alkylating agent afforded an exclusively N-alkylation product 359. 202 Polycyclic framework BABAR-Phos-type phosphiranes allowed the synthesis of various platinum(0) com-…”
Section: Scheme 58 Reactions Of Tris(trimethylsilyl)silyllithium Withmentioning
confidence: 99%